OPTIMIZATION OF SOLAR ENERGY UTILIZATION USING CONCENTRATED SOLAR HYBRID ENERGY HARVESTER (CSHEH) BASED ON SMART SOLAR PANEL AND CONCENTRATED THERMOELECTRIC GENERATOR - Afandi, Moh; Chandrarini, Dinda Dwi (MATTER: International Journal of Science and Technology, 2015)
Many forms of community activities and national industrial sector are highly dependent on the availability of electrical energy. Unfortunately, at the end of 2014 the electrification ratio in Indonesia is only 80.5%. On the other hand, Indonesia is a tropical country that has high intensity of sunlight almost 10 hours per day throughout the year. Indonesia has a solar energy intensity of 4.0-4.9 kWh/m2. This condition is potentially to be used as an alternative source of electrical energy to cover the electricity shortage, particularly in areas which is difficult to reach by existing electricity power. This paper will discuss about optimization of solar energy utilization through Concentrated Solar Hybrid Energy Harvester (CSHEH). CSHEH consists of Smart Solar Panel and Thermoelectric Generator. CSHEH is able to convert the two energy generated by the sun into electrical energy that is photon energy through the photovoltaic effect of solar panel and heat energy through Seebeck effect of thermoelectric. In case, CSHEH is able to provide an alternative solution to produce electricity, especially in isolated areas. As well as being stand alone, the advantages of CSHEH also does not require operating costs, and environmentally friendly because it just utilize solar energy as a source.